Bisoprolol and sotalol for maintaining sinus rhythm in patients with paroxysmal atrial fibrillation and chronic heart failure - S. N. Tereshchenko; Yu. A. Uteshev; M. N. Morozova; N. G. Chuich; A. G. Kochetov (Кардиоваскулярная терапия и профилактика)
Aim. To compare sotalol and bisoprolol efficacy for post-cardioconversion sinus rhythm maintaining in patients with chronic heart failure (CHF) and paroxysmal atrial fibrillation (AF). Material and methods. For 6 months, 45 patients (mean age 60.3±3.2 years) with non-rheumatic AF were observed. In individuals with CHF and paroxysmal AF, after restoring sinus rhythm, preventive antiarrhythmic therapy included sotalol (mean daily dose 160 mg; Group I, n=23) and bisoprolol (mean daily dose 7.5 mg; Group II, n=22). Results. In one patient from Group II and 3 patients from Group I (4.5% and 13%, respectively), AF became permanent. CHF functional class decreased by 7% in Group I, and by 10.2% in Group II. Six-minute walking test results improved by 10.2% and 9.3%; left ventricular ejection fraction increased by 1.3% and 9.3%; left atrium size reduced by 2.1% and 6.8%, respectively. In sotalol group, functional activity of β-adrenoreceptors (β-AR) increased by 16.5% (р>0.05), in bisoprolol group, it significantly reduced by 34% (р<0.05). There was direct correlation between β-AR and heart rate (r=0.58, р<0.01), and inverse linear correlation between β-AR and physical stress tolerance improvement (r=-0.43, р<0.05). Conclusion. Sotalol and bisoprolol were equally effective in maintaining restored sinus rhythm in patients with CHF and paroxysmal AF.